2016
DOI: 10.1108/ijchm-05-2014-0231
|View full text |Cite
|
Sign up to set email alerts
|

Social innovation success factors: hospitality and tourism social enterprises

Abstract: Purpose This paper aims to contribute to the existing literature on social enterprises and business model innovation. Particularly, it sheds some light on those factors that turn a social innovation initiative into a success, both in terms of meeting social needs and achieving economic sustainability. Design/methodology/approach By using a grounded theory approach, an inductive comparative case study is conducted. Two work integration social enterprises in the hospitality and tourism sector are selected. Bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 55 publications
0
60
0
2
Order By: Relevance
“…The primary goal of social entrepreneurship is to create social and economic values, and not only to make a profit for the owners of enterprises and other stakeholders. Sustainability of social enterprises depends on the ability of an enterprise to cover its total business costs and obtain an adequate market share [33]. Social entrepreneurship is not a new type of entrepreneurship, but it deals exclusively with environmental issues [16].…”
Section: Relationship Between Social Entrepreneurship and Green Hotelsmentioning
confidence: 99%
“…The primary goal of social entrepreneurship is to create social and economic values, and not only to make a profit for the owners of enterprises and other stakeholders. Sustainability of social enterprises depends on the ability of an enterprise to cover its total business costs and obtain an adequate market share [33]. Social entrepreneurship is not a new type of entrepreneurship, but it deals exclusively with environmental issues [16].…”
Section: Relationship Between Social Entrepreneurship and Green Hotelsmentioning
confidence: 99%
“…In particular, contributions address the challenges of integrating sustainability in destination business model design (Mihalič, Žabkar, & Cvelbar, 2012;Scheepens, Vogtländer, & Brezet, 2016) and hospitality management practices (Bohdanowicz & Zientara, 2009;Høgevold, Svensson, & Padin, 2015;Sarkar & Sinha, 2015). Contributions focusing on innovation investigated adoption and commercialization of new products and services by means of improved and new business models (Alegre & Berbegal-Mirabent, 2016;Hojman & Hunter-Jones, 2012;Huang, Lee, & Lee, 2009;Rusu, 2016;Souto, 2015). Side topics explored by few authors include the role of ownership structures at festivals (Andersson & Getz, 2009), competing taxation systems between destinations and online travel companies (Schiller, 2011), and changes in consumer behavior stemming from collaborative consumption (Kathan, Matzler, & Veider, 2016).…”
Section: Configurations In Tourism Sectorsmentioning
confidence: 99%
“…Related sustainability efforts and benefits mainly referred to maintaining or improving the (ecological) environment for future generations (Mihalič et al, 2012) and different aspects of economic growth. This growth benefits residents if it stems from ecofriendly destination development (Sarkar & Sinha, 2015), inclusion of disadvantaged residents (Alegre & Berbegal-Mirabent, 2016), builds upon collaborative consumption (Kathan et al, 2016) or contributes to multiple sustainability aspects at once (Mihalič et al, 2012;Scheepens et al, 2016). Finally, despite value (co-)creation for specific customers being a focus of business model research, only two studies highlighted their role and benefits in tourism contexts: Koukopoulos and Styliaras (2013) discuss new tourist experiences stemming from the use of smartphone apps and Pine and Gilmore (2016) discuss how customer experience should be incorporated in "modern" business offerings.…”
Section: Relevance and Recipients Of Different Value Typesmentioning
confidence: 99%
“…Additionally, Hilman and Kaliappen (2014) mentioned that innovation in the hospitality industry allows the organization to achieve economies of scale, reducing the cost and gain market share. Alegre and Berbegal-Mirabent (2016) found management, core and support process in the restaurant industry that requires innovations in managing the costs. Acquaah (2011) find that low-cost strategies have a strong positive effect on performance; Acquaah and Agyapong (2015), Dadzie et al (2013) and Agyapong and Boamah (2013) found that strategic cost leadership does not extract strong effects on firm performance.…”
Section: Introductionmentioning
confidence: 99%